2022
DOI: 10.33736/jcshd.4520.2022
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Online Learning Experiences for ESL Speaking Activities

Abstract: Performing speaking tasks via online learning can be challenging for first-year university students. This quantitative study explored the students' perceptions of online learning experiences, challenges, and strategies in implementing English speaking activities. 127 out of 315 students responded to the questionnaire, which involved asking for information on students' backgrounds, perceptions of online platforms, online learning adoption and difficulties in implementing speaking tasks via online learning. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The biological perspective examines how numerous physiological occurrences influence a person's behavior (Maysuroh, Wati, Dwimaulani, Yusri, & Sholihah, 2022), feelings, and thoughts (Iftanti, Imelda, & Yunita, 2023). Electrical impulses move through the nervous system's intricate circuitry (Fauzi, Ambi, Madaud, & Unin, 2022). The internal organs are told to speed up or slow down their activity by a set of hormones found throughout the circulation (Wulandari, Tantra, & Santosa, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological perspective examines how numerous physiological occurrences influence a person's behavior (Maysuroh, Wati, Dwimaulani, Yusri, & Sholihah, 2022), feelings, and thoughts (Iftanti, Imelda, & Yunita, 2023). Electrical impulses move through the nervous system's intricate circuitry (Fauzi, Ambi, Madaud, & Unin, 2022). The internal organs are told to speed up or slow down their activity by a set of hormones found throughout the circulation (Wulandari, Tantra, & Santosa, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The internal organs are told to speed up or slow down their activity by a set of hormones found throughout the circulation (Wulandari, Tantra, & Santosa, 2021). Psychologists that investigate perceptions (Fauzi et al, 2022), memories, and behavior from a biological perspective look at how physical events interact with events in the outside world to form perceptions, memories, and behavior (Zainal & Yunus, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, many of them fail to become fluent in these 11 years (It is aligned to what Nik Fauzi, Ambi, Abang Madaud and Unin (2022) claimed that university physical classroom shutdown and new online learning practices have had an influence on the educational opportunities of this group of first-year students even though they have studied English in Malaysian primary and secondary schools for 11 years. Hunt and Beglar (2005), as cited in Nik Fauzi et al (2022), indicated that English learners' vocabulary learning is consistently poor. The Star Online Publication (2022) reported that the Central Bank of Malaysia discovered more than 10% of adolescents are jobless.…”
Section: Introductionmentioning
confidence: 99%
“…They strictly adhere to what is written in the books. Their goal is to complete the book's contents [3] .They do not care if the lesson is exciting or if the students can follow or understand it. Students become less motivated and enthusiastic, and slow learners become frustrated and give up.…”
Section: Introductionmentioning
confidence: 99%